1984
DOI: 10.1080/00365521.1984.12005706
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chemical Sympathectomy on Insulin-Stimulated Gastric Secretion in Dogs

Abstract: Administration of 6-hydroxydopamine (6-OHDA) causes selective acute degeneration of the adrenergic nerve terminals--that is, a reversible chemical sympathectomy. The effect of this drug was studied on the insulin-stimulated gastric secretion. Insulin-stimulated (0.15-0.4 IU/kg) gastric acid and pepsin output and serum gastrin were measured before and after 6-OHDA treatment (40 mg/kg) in gastric fistula dogs. Chemical sympathectomy resulted in a highly significant increase in acid and pepsin secretion. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Chemical sympathectomy with 6-OHDA causes complete sympathectomy of the gastric mucosa (Thoenen and Tranzer, 1968). As sympathetic innervation of the stomach inhibits gastric-acid secretion, chemical sympathectomy resulted in a highly significant increase in gastric-acid secretion (Grabner et al, 1984). Larson et al (1984 reported that chemical sympathectomy increased acid secretion in response to submaximal doses of pentagastrin.…”
Section: And Palmer and Humphreysmentioning
confidence: 99%
“…Chemical sympathectomy with 6-OHDA causes complete sympathectomy of the gastric mucosa (Thoenen and Tranzer, 1968). As sympathetic innervation of the stomach inhibits gastric-acid secretion, chemical sympathectomy resulted in a highly significant increase in gastric-acid secretion (Grabner et al, 1984). Larson et al (1984 reported that chemical sympathectomy increased acid secretion in response to submaximal doses of pentagastrin.…”
Section: And Palmer and Humphreysmentioning
confidence: 99%